Talking to the beat: Six-year-olds' use of stroke-defined non-referential gestures. Issue 2 (April 2018) - Mathew, Mili; Yuen, Ivan; Demuth, Katherine
Children are known to use different types of referential gestures (e.g., deictic, iconic) from a very young age. In contrast, their use of non-referential gestures is not well established. This study investigated the use of stroke-defined non-referential 'beat' gestures in a story-retelling and an exposition task by twelve 6-year-olds, an age at which proficiency in discourse is beginning to develop. The goals of the study were to (1) establish if children this age use stroke-defined beats, (2) determine whether the two discourse types influence the incidence of stroke-defined beats, and (3) examine the extent to which stroke-defined beats co-occur with lexical words or pitch accents. The results showed that nine of the children produced at least one beat gesture with a well-defined stroke phase, and that the frequency of the stroke-defined beat gesture use did not differ significantly between the two tasks. Stroke-defined beats occurred more often on lexical words than function words, but they did not co-occur more often with a pitch accent, suggesting its potential link with pitch accents for emphasis. This study therefore provides support for children's 'prosodic' use of gesture – a function which may become more common as discourse abilities develop.